(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate external quality assessment (EQA) and internal quality control (IQC) of several biochemical tests and determine the error rate of related factors at the Laboratory Department - Binh Thuan Traditional Medicine and Rehabilitation Hospital in 2024. Methods: Cross-sectional descriptive study. External and internal quality control results of 10 biochemical parameters were evaluated on the Erba XL 200 automated biochemistry analyzer from April to September 2024. Randox control serum at 2 concentration levels was used to assess precision, trueness, and accuracy according to the Westgard Desirable Biological Variation Database. External quality assessment was evaluated using the Standard Deviation Index (SDI) and Target Score. Errors were classified into 4 causal groups (equipment, reagents, personnel, environment) based on daily internal quality control incident records. Results: Most biochemical parameters had CV% within allowable limits, except for Creatinine, which failed to meet CV% criteria across all 6 months, and HDL-C, which showed a Bias-D of 19.2% — exceeding the allowable threshold by nearly 3.5-fold. External quality assessment achieved 91.7% of results with SDI < 2.0. Equipment and reagents were the two primary error-contributing factors, accounting for 43.6% and 38.2% respectively. Conclusion: Overall external and internal quality control performance was satisfactory; however, Creatinine and HDL-C require priority improvement. Equipment and reagent-related errors were 2–3 times higher than those attributable to personnel and environmental factors.